Antecedentes ao sucesso na operação de PMO’s: um modelo estrutural - Magalhães, Diego Marlos Designe (2012)
This explanatory-exploratory study aims to determine the key success factors for the operation of PMOs in organizations. As a way to reach this target, firstly, it was developed an adequate literature to: (a) conceptualize Project Management; (b) identify the different ways of PMO action; (c) identify the key success factor for PMOs operation; (d) identify the group of factors that impacts the success of PMOs; (e) develop a meta-model including the factors that impact and define the operation success of PMOs; (f) develop a survey as a tool for collecting data and (g) develop adequate methodology to the structural equation use. The survey application (collecting data tool) resulted on 553 valid answers, being filled for project management specialists. In total, 489 of them were Brazilians, and 64 of them were foreigners project managers from several countries in the world. After collecting the data, the study applied exploratory factorial analysis (EFA), confirmatory factorial analysis (CFA) and structural equation modeling (SEM) to test the proposed theoretical model. The theoretical model initially developed was not supported, notwithstanding had been obtained some adjustments necessary, as well as supported by adequate theoretical justification. Even setting the model, the final result says that it explains nearly 7% of the therefrom model proposed for the success of PMOs operation.